The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/feduc.2022.753710
|View full text |Cite
|
Sign up to set email alerts
|

Right Cortical Activation During Generation of Creative Insights: An Electroencephalographic Study of Coaching

Abstract: Coaching as a human development methodology has been demonstrating its results for more than four decades. Even so, the level of confusion about its essence and its lack of a definitive theoretical and methodological framework has caused its effectiveness to be questioned. Although studies on coaching with neuroimaging methodologies have been developed, there is no recent evidence about the brain changes in electroencephalographic (EEG) activity during a coaching session. The present research aims to make a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…The study demonstrated that the coaching interventions produced an increase in these neurological indicators, signaling an improvement in the coachees' decision-making ability [140]. A subsequent study carried out by Bartolomé and colleagues [146] compared the effectiveness of directive and non-directive coaching styles in enhancing the coachee's ability to develop creative insights (i.e., divergent thinking), considered an effect of strengthening problem-solving skills. The non-directive coaching style showed greater activation of the alpha and theta bands in the right temporal region and alpha, theta, and gamma in the right parietal area.…”
Section: Neurocoaching: a Neuroscientific Approach To Coachingmentioning
confidence: 95%
See 1 more Smart Citation
“…The study demonstrated that the coaching interventions produced an increase in these neurological indicators, signaling an improvement in the coachees' decision-making ability [140]. A subsequent study carried out by Bartolomé and colleagues [146] compared the effectiveness of directive and non-directive coaching styles in enhancing the coachee's ability to develop creative insights (i.e., divergent thinking), considered an effect of strengthening problem-solving skills. The non-directive coaching style showed greater activation of the alpha and theta bands in the right temporal region and alpha, theta, and gamma in the right parietal area.…”
Section: Neurocoaching: a Neuroscientific Approach To Coachingmentioning
confidence: 95%
“…The non-directive coaching style showed greater activation of the alpha and theta bands in the right temporal region and alpha, theta, and gamma in the right parietal area. Such brain activations, which are associated with processes of creative ideation [147][148][149][150], metacognition [151,152], and problem solving [153,154], provided neurophysiological evidence that coaching can enhance insight-based problem-solving skills [146].…”
Section: Neurocoaching: a Neuroscientific Approach To Coachingmentioning
confidence: 99%
“…36 Interestingly, in an MRI study comparing EEG activity of nondirective coaching (as described in this article) and directive coaching (instructing and advising), nondirective coaching showed EEG activity consistent with higher generation of insights than directive coaching. 37 Examples of integration, and insight generation, in the context of lifestyle medicine include:…”
Section: Generating Potential For Changementioning
confidence: 99%
“…Additional insights on the generation of creativity/insight that may occur during a coaching session can be gained with the study of non-directive coaching (Bartolome et al, 2022 ). Non-directive coaching (NDC), is a client-centered conversation oriented to reflection, wherein the coach mainly observes and listens to the client speaking, mirroring what the client says, and asking open ended questions, enhancing the client's own potential for reflection (Bartolome et al, 2022 ). When considering the neurophysiological signature of NDC, significant activation in networks of the right parieto-temporal region occurred during the generation of (creative) insights (Bartolome et al, 2022 ).…”
Section: What Is Executive Coaching?mentioning
confidence: 99%